2021
DOI: 10.1103/physrevb.104.125138
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phases of a frustrated spin-1 system: The 5/7 skewed ladder

Abstract: Quantum phases of a frustrated spin-1 system: The 5/7 skewed ladder (2021) Physical Review B, 104 (12), art. no. 125138, .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The HAF spin-1/2 system on 5/7, 3/4, 3/5 and 5/5 skewed ladders shows interesting magnetic and non-magnetic QPT in the parameter space of the rung and the leg spin exchange constants [44,45]. Recent work on HAF spin-1 on 5/7 [46], 3/4 and 3/5 [47] skewed ladders has also shown existence of similar magnetic and non-magnetic phase transitions. The quantum phases of HAF spin-1/2 system on 3/4, 5/5 and 3/5 skewed ladders studied at finite external axial magnetic field B are found to show various magnetic plateau phases which follow the Oshikawa, Yamanaka, and Affleck (OYA) [48] rule, in the B − J 1 − J 2 parameter space.…”
Section: Introductionmentioning
confidence: 89%
“…The HAF spin-1/2 system on 5/7, 3/4, 3/5 and 5/5 skewed ladders shows interesting magnetic and non-magnetic QPT in the parameter space of the rung and the leg spin exchange constants [44,45]. Recent work on HAF spin-1 on 5/7 [46], 3/4 and 3/5 [47] skewed ladders has also shown existence of similar magnetic and non-magnetic phase transitions. The quantum phases of HAF spin-1/2 system on 3/4, 5/5 and 3/5 skewed ladders studied at finite external axial magnetic field B are found to show various magnetic plateau phases which follow the Oshikawa, Yamanaka, and Affleck (OYA) [48] rule, in the B − J 1 − J 2 parameter space.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, Dey et.al. carried out the magnetization study of isotropic Heisenberg spin-1/2 on a 5/7-skewed ladder and showed multiple plateau phases with field h [46]. They show that plateau phases are the consequences of gaps in the spectrum, and these plateau phases can be explained in terms of Oshikawa, Yamanaka, and Affleck (OYA) criterion [47].…”
Section: Introductionmentioning
confidence: 99%
“…Another type of anisotropic spin-1/2 ladder is the Kitaev-Heisenberg model on a two leg ladder where the GS has many exotic quantum phases [36]. Many spin-1/2 ladder systems with isotropic and anisotropic exchange interactions have been extensively studied under magnetic field and are reported to exhibit some of the magnetic plateaus and jumps [39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Japaridze et al studied a two-leg spin-1 2 ladder system with leg interaction J and alternate rung as J + ⊥ , J − ⊥ in presence of a longitudinal field h. They have shown that the system shows a zero magnetization up to h − c1 , a plateau at half of the saturation magnetization between h + c1 and h − c2 and full saturation achieved at h + c2 [53].…”
Section: Introductionmentioning
confidence: 99%
“…The Heisenberg antiferromagnetic (HAF) spin-1/2 system on 5/7, 3/4, 3/5 and 5/5 skewed ladders shows interesting magnetic and non-magnetic QPT in the parameter space of the rung and the leg spin exchange constants [44,45]. Recent work on HAF spin-1 on 5/7 [46], 3/4 and 3/5 [47] skewed ladders has also shown existence of similar magnetic and non-magnetic phase transitions. The quantum phases of HAF spin-1/2 system on 3/4, 5/5 and 3/5 skewed ladders studied at finite external axial magnetic field B are found to show various magnetic plateau phases which follow the Oshikawa, Yamanaka, and Affleck (OYA) [48] rule, in the B − J 1 − J 2 parameter space.…”
Section: Introductionmentioning
confidence: 99%